Selective glycerol esterification to monolaurate over ZrO2/MCM-41 catalysts prepared using impregnation and precipitation methods. Issue 5 (4th May 2022) - Abdullah, Ahmad Zuhairi; Ghazali, Natasha; Hoo, Peng Yong; Basir, Nor Irwin
Abstract: In order to develop an active and selective catalyst for the selective esterification of glycerol with fatty acid to monoglycerides, zirconia was incorporated into mesoporous MCM-41 support using two methods, i.e., impregnation and precipitation. The zirconia loading was varied between 10 and 30 wt. % to demonstrate its effect on the properties and activity of the modified catalysts. The catalysts were then characterized by N2 -adsorption surface analysis, SEM/EDX, FTIR, and TGA. The catalytic activity was then demonstrated in the selective esterification of glycerol with either lauric or palmitic acid at 160 °C for 6 h with glycerol/fatty acid molar ratios of 1:1, 4:1, and 6:1 and catalyst loadings up to 5 wt. %. Fatty acid conversion as well as monoglyceride selectivity and yield were monitored to measure the extent of reaction leading to the formation of the desired products. Correlations between the activity and the characteristics of the catalysts under various reaction conditions were successfully established. Relatively slower zirconia incorporation in the impregnation method caused more internal incorporation of the acidic component. MCM-41 catalyst with 30 wt. % zirconia loading that was prepared by impregnation method with a surface area of 589 m 2 /g and an acid site concentration of 6.83 µmol/g showed a lauric acid conversion of 98.6% and a monolaurin selectivity of 57.2%. An increase in the molar ratio exceeding 4:1 did not bring about the desired effect due to the dilution effect of the limiting reactant. Lower activity was demonstrated by stearic acid due to its higher molecular size and viscosity to mainly affect the mass transfer during the reaction.